Painting Deep Time: Encountering Landforms’ Alterity and Phusis Through Phenomenology and Oil Painting - Behrisch, Tanya J. (Phenomenology & practice, 2021)
The practice of oil painting landforms, rocks and sea water in Jervis Inlet, British Columbia (BC) puts me in dialogue with land’s resistant alterity.  By closely attuning to landforms, and by stepping back and blurring my focus at regular intervals while practicing oil painting of landforms, I experience phusis of land and of my painting.  Through self-concealment and emergence, land alternates between revealing and enfolding its character, resisting my human comprehension but speaking to more-than-human elements in myself.  The slow accretive process of oil painting lends itself to phenomenological research, taking days and weeks for paint to dry before new layers can be applied.  This slowness produces phusis within me as an artist, as I am forced to withdraw from the painting while its layers dry and we reassume an unfamiliarity with one another as dual subjects.  Through oil painting, landforms’ alterity shifts towards familiarity.  Earth’s elements originate in deep time, pre-dating human experience.  Cycling within me is a repository of minerals, water, and salinity originating in deep time.  This draws attention to alterity within my own body.  By practicing phenomenological research through painting landforms, I encounter the phenomenological paradox of deep time and come face-to-face with the originary elemental origin I share with landforms.